Staying Alive: A Survival Manual for the Liberal Arts - Fradenburg, L.O. Aranye (punctum books, 2013)
Staying Alive: A Survival Manual for the Liberal Arts fiercely defends the liberal arts in and from an age of neoliberal capital and techno-corporatization run amok, arguing that the public university's purpose is not vocational training, but rather the cultivation of what Fradenburg calls "artfulness," including the art of making knowledge. In addition to sustained critical and creative thinking, the humanities develop the mind's capacities for real-time improvisational communication and interpretation, without which we can neither thrive nor survive. Humanist pedagogy and research use play, experimentation and intersubjective exchange to foster forms of artfulness critical to the future of our species. From perception to reality-testing to concept-formation and logic, the arts and humanities teach us to see, hear and respond more keenly, and to imagine, or "model," new futures and possibilities. Innovation of all kinds, technological or artistic, depends on the enhancement of the skills proper to staying alive